Determinants of Efficiency of Tax’s Collection in Oman - Alsarmi, Yousuf Nasser Amur; Ahemed, Essia Ries (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2022)
This study examines the relationship between determinants of tax efficiency (tax awareness, electronic procedures and auditing procedures) and efficiency of tax collection in Oman. The research uses method of a quantitative method via survey 150 usable data based on tax inspectors of Tax Authority in Oman. The hypotheses of the present study utilized its variables via using Smart PLS and SPSS statistical tools. The findings revealed that a positive and significant link between tax awareness and efficiency.  As well as, the findings revealed other possible determinants (electronic procedures and auditing procedures) has a insignificant influence on efficiency of tax collection in Omani Tax Authority. The model of the current research might be beneficial to realize determinants of tax efficiency to growth the  effective of tax collection. Yet, practicing tax inspectors might understand tax awareness to improve firm effectiveness.